Structural anomalies in tobelite-2M2 explained by high resolution and analytical electron microscopy. (1st February 2016) - Capitani, G. C.; Schingaro, E.; Lacalamita, M.; Mesto, E.; Scordari, F.
A transmission electron microscopy (TEM) investigation was undertaken in order to elucidate the nature of the structural disorder in a tobelite specimen from the sedimentary rocks of the Armorican sandstones (western France). This structural disorder may be the origin of residual electron-density maxima in difference-Fourier maps reported previously in single-crystal XRD studies of tobelite. The TEM investigation of tobelite confirmed that it is the 2M2 polytype in subfamily-B, but the ordered sequence is interrupted by numerous stacking faults parallel to (001), for which the stacking vectors belong to both subfamilies-A and -B of mica polytypes, with a prevalence of the latter. Chemical heterogeneity depending on the Si/Al ratio and Na and Mg concentration was observed at the nanoscale among different mica lamellae in a single crystal. The observed variations are consistent with a change in mica chemistry leading to interlayer vacancies which may cause shortening of the interlayer separation, as revealed by the single-crystal structure refinements.